The analysis of response in crop and livestock production - Dillon, John L. (Pergamon international library of science, technology, engineering, and social studies., 1990)
This text provides an introductory outline of the analytical principles involved in appraising the efficiency of crop-fertilizer and livestock-feed response. It provides students of both agricultural science and economics with a simple but formal exposition of the why, how and wherefore of the principles of crop and livestock analysis, thereby helping to further co-operative effort among biological and economic researchers. The third edition has been updated and revised thoroughly. `The book is very nicely produced, easy to read, and free from errors and innacuracies ... Dillon and Anderson's text is excellent value.' Outlook on Agriculture, 1990.